Genome analysis and prevalence of SARS-CoV-2 Indonesian variants and the correlation with the outbreak timeline - Maria Prevyolita Indra Muliawan; Timotius Christopher Tantokusumo; Amalda Siti Anisa; Kholis Abdurachim Audah (Acta Biochimica Indonesiana)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has undergone multiple mutations, leading to the development of various variants.